Fertility and the plough - Alberto Alesina; Paola Giuliano; Nathan Nunn (Institute for the Study of Labor (IZA), 2011)
The current study finds that societies which historically engaged in plough agriculture today have lower fertility. We argue, and provide ethnographic evidence, that the finding is explained by the fact that with plough agriculture, children, like women, are relatively less useful in the field. The plough requires strength and eliminates the need for weeding, a task particularly suitable for women and children. This in turn generates a preference for fewer children, lowering fertility.
urn:nbn:de:101:1-201104113752
Keywords: J13; O13; 330; fertility; plough; cultural norms; Ackerbau; Weibliche Arbeitskräfte; Familienplanung; Fruchtbarkeit; Kulturelle Identität